Relationship Between Sex-Pili Formation and Macarbomycin Sensitivity in Escherichia coli - Iyobe, Shizuko (1971)
The presence in Escherichia coli strains of derepressed sex factors determining F-type pili formation was found to increase their sensitivity to macarbomycin.